The effects of Symbiodinium (Pyrrhophyta) identity on growth, survivorship, and thermal tolerance of newly settled coral recruits. Issue 6 (8th November 2016) - McIlroy, Shelby E.; Gillette, Phillip; Cunning, Ross; Klueter, Anke; Capo, Tom; Baker, Andrew C.; Coffroth, Mary Alice
Abstract : For many coral species, the obligate association with phylogenetically diverse algal endosymbiont species is dynamic in time and space. Here, we used controlled laboratory inoculations of newly settled, aposymbiotic corals ( Orbicella faveolata ) with two cultured species of algal symbiont ( Symbiodinium microadriaticum and S. minutum ) to examine the role of symbiont identity on growth, survivorship, and thermal tolerance of the coral holobiont. We evaluated these data in the context of Symbiodinium photophysiology for 9 months post‐settlement and also during a 5‐d period of elevated temperatures Our data show that recruits that were inoculated with S. minutum grew significantly slower than those inoculated with S. microadriaticum (occasionally co‐occurring with S. minutum ), but that there was no difference in survivorship of O. faveolata polyps infected with Symbiodinium . However, photophysiological metrics (∆Fv/F′m, the efficiency with which available light is used to drive photosynthesis and α, the maximum light utilization coefficient) were higher in those slower growing recruits containing S. minutum . These findings suggest that light use (i.e., photophysiology) and carbon acquisition by the coral host (i.e., host growth) are decoupled, but did not distinguish the source of this difference. Neither Symbiodinium treatment demonstrated a significant negative effect of a 5‐d exposure to temperatures as high as 32°C under low light conditions similar to those measured at settlement habitats.